A study of the regulatory framework on electronic commerce and consumer protection in Malaysia / Dr. Kiranjit Kaur … [et al.] - Kaur, Kiranjit (Dr.) Associate Professor; Iyer, Mangalam Gopala (Associate Professor); Abdul Jabar, Noraziah; Abdul Hamid, Norliza (2005)
This study examines first, existing legislation governing e-commerce transactions in Malaysia, and second, the redress mechanisms available to online retailers and customers. Various legislations that affect Internet related activities, whether directly or indirectly, were examined to see the level of protection provided to consumers. The strengths and weaknesses that exist in them were also analysed. In essence, an e-commerce consumer is like any other buyer except that the method of shopping is different. Thus, the consumer should be afforded the same legal protection. Based on related studies conducted by the researchers in Malaysia, several consumers thought that they are still not adequately protected. For instance, the Consumer Protection Act 1999 is to protect consumers against misleading and deceptive conduct, false representation, and unfair trade practices. However, e-commerce consumers are outside the ambit of the Act unless otherwise prescribed by the Minister. The study also examined methods of settling disputes other than by going to courts through Alternative Dispute Resolution including arbitration, mediation and conciliation. In its effort to build confidence and trust in e-commerce transactions, the government has proposed two new Bills: the Electronic Commerce Bill and the Data Protection Bill. Both Bills adopt the principles of the UNCITRAL Model Law on Electronic Commerce 1996. The provisions are more comprehensive and to a certain extent may resolve matters that were not covered by other statutes. The researchers propose that these two Bills be passed as speedily as possible to enhance e-commerce activities in Malaysia.